The Linguistic Thought Between Al-Jurjani and Chomsky Through the Theories of Nazm and Generative Grammar - Hassan, Ahmed Osman Fedail (Journal of Arabic Education and Linguistic, 2024)
This study aims to explore the points of convergence and similarity between the linguistic thought of the Arab scholar ʿAbd al-Qāhir al-Jurjānī and contemporary linguistic theories, particularly the contributions of scholars in the field of transformational-generative linguistics. This exploration aligns with the call to revisit and reinterpret Arab intellectual heritage in light of contemporary linguistic concepts, thereby creating a meaningful connection between the two to enrich modern linguistic studies across diverse contexts. The research focuses on ʿAbd al-Qāhir al-Jurjānī, the proponent of the "Nazm" theory, to compare his ideas with the transformational-generative theory due to the significant points of alignment between the two frameworks. For instance, Chomsky’s theory resembles al-Jurjānī’s thought in its conceptualization of "precedence and succession," as it emphasizes the primacy of certain linguistic elements over others within a syntactic structure. Moreover, Chomsky’s theory has become a dominant paradigm in linguistic studies, and no linguistic school has refrained from engaging with or positioning itself in relation to his ideas.